Considerações sobre o papel da sociofonética na comparação forense de locutores - Gonçalves, Cintia Schivinscki; Brescancini, Cláudia Regina (Language and Law / Linguagem e Direito, 2017)
This study examines the field of Forensic Linguistics, from the perspective of Sociophonetics. In the paper we present sociolinguistic and phonetic considerations which are relevant to the work in Forensic Phonetics, with an emphasis on what happens at the official level, specifically with reference to the expertise of speaker comparison. The objective is to lay the foundations for the legitimate linguistic descriptions that are used in this type of investigation confrontation aimed at determining the origin of a speaker from his/her voice/speech. Issues concerning the relevance of the concept of ‘community of practice’ in the context of forensics are approached, as well as the application of sociolinguistic interviews, the stylistic variation present in the material for analysis, and linguistic elements of a sociophonetic nature, commonly used as technical and comparative parameters. This analysis can help improve the practice of speaker comparison, and contribute to the quality of the resulting technical production, namely the technical report.